Does Functional Imaging Play a Role in Pre-Operative Diagnosis of Brain Tumours? - Oancea, Alexandra A.; Saleh, Christian; Cordier, Dominik; Schoepfer, Raphaela; Lieb, Johanna (Fortschritte der Neurologie · Psychiatrie, 2023)
Although there is a large variability in the neural organization of language function between individuals, there is an ongoing debate about functional imaging as a standard procedure in the preoperative setting of brain tumors. Brain mapping of the language centers differs from individual to individual in multilingual patients and changes in its architecture may occur as a result of neuroplasticity induced by a mass lesion. This article discusses the role of functional imaging in the preoperative setting.
Keywords: Functional imaging; Brain tumor; Brain mapping; Speech areas